Предмет: Алгебра,
автор: da6ulika
x^{2} y^{2} -9 y^{2} = y^{2} (x-3)(x+3) разложите на множители
Ответы
Автор ответа:
0
X^{2} y^{2} -9 y^{2} = y^{2} (x-3)(x+3)
X^{2}y^{2} -9 y^{2}=y^{2} (х^{2}+3х-3х-9)= X^{2}-9 y^{2}=y^{2}X^{2}+3хy^{2}-3хy^{2}-9 y^{2}=X^{2} y^{2} -9 y^{2}
X^{2}y^{2} -9 y^{2}=y^{2} (х^{2}+3х-3х-9)= X^{2}-9 y^{2}=y^{2}X^{2}+3хy^{2}-3хy^{2}-9 y^{2}=X^{2} y^{2} -9 y^{2}
Похожие вопросы
Предмет: Биология,
автор: katepasihna
Предмет: Физика,
автор: deatshot9989
Предмет: Русский язык,
автор: npapav03
Предмет: Математика,
автор: 456951753285